Virtual Screening, Molecular Docking and Molecular Dynamics Simulation of Bioactive Compounds from Various Indonesian Medicinal Plants as Potential Inhibitors of Human Papillomavirus Type 16 E6 Protein in Cervical Cancer Development - Arief Hidayatullah; Diana Widiastuti; Wira Eka Putra; Muhaimin Rifa’i; Muhammad Fikri Heikal; Sustiprijatno (Tropical Life Sciences Research, 2025)
Infection of keratinocytes by high-risk human papillomavirus (HPV) strains, notably HPV16, is responsible for the onset of cervical cancer. The E6 protein serves as a pivotal oncoprotein implicated in the progression of cancer. We utilised a virtual screening method to identify bioactive compounds in a variety of commonly used medicinal plants in Indonesia. All the top five compounds bind to a single binding site on the E6 major hydrophobic groove, which corresponds to the binding site for the E6AP and IRF3’s LxxLL motifs. They are expected to function as competitive inhibitors, inhibiting the development of the E6-E6AP and E6-IRF3 complexes, which limit p53 degradation and therefore cell proliferation, thus preserving the innate immune response to HPV16 infection. Asarinin and thiazolo[3,2-a]benzimidazole-3(2H)-one,2-(2-fluorobenzylideno)-7,8-dimethyl were predicted to be the most effective compounds in this research owing to their strong affinity for and persistent interactions with the E6 major hydrophobic groove, particularly in comparison to pharmacological controls.